Revision of the genus Iphiplateia (Crustacea, Amphipoda, Phliantidae) from Australia - Coleman, Ch. Oliver; Lowry, James K. (Zootaxa, 2012)
The new species Iphiplateia marleneae, Iphiplateia jakei and Iphiplateia verenaae are described and the similar taxonIphiplateia whiteleggei is redescribed. Iphiplateia marleneae differs from I. whiteleggei in the subcircular body shape, theslender articles 4–5 of the peduncle of antenna 2, the medially expanded maxilliped palp articles 2 and 3, notches on themerus of all pereopods and pereopod 7 basis is drawn out into a subacute angle. Both I. jakei and I. verenaae differ fromI. marleneae and I. whiteleggei in having a dorsal pereon keel. Iphiplateia verenaae can be distinguished from I. jakei by its significantly smaller basis of pereopod 7.